Capsule shell of pharmaceutical products in Malaysia; the sources and Halal status - Tajul Ariffin, Muhammad Farahi 'Arif; Shamsudin, Siti Hadijah; Wan Sulaiman, Wan Mohd. Azizi; Thiruvanackan, Kobu (worldconferences.net, 2018)
Malaysia is the first country in the world which has successfully come out with a general guideline for halal pharmaceuticals. As a new sector, halal pharmaceuticals offers a lot of opportunities for industrial player, but also challenges that need to be accepted. Gelatine is one of the big issues in producing halal pharmaceutical products. 46% of gelatine worldwide is produced from pig-skin, and this source is prohibited for Muslims consumption. Pharmaceuticals and nutraceuticals are the second and third biggest application categories of gelatine after food, accounting for 26 percent and 21 percent respectively of the total market, implying a $1.3 billion market in 2015. One of the common usage of gelatine in pharmaceutical sector is for production of capsule shell. The study aims to produce a statistic on the sources of capsule shell and their halal status for all pharmaceutical products registered in Malaysia. METHODOLOGY: A text analytical method, Information Extraction Technique has been applied, to extract the data from different national databases on capsule shell sources of pharmaceutical products and their halal status. RESULT & DISCUSSION: 3085 pharmaceutical products in capsule dosage form have been included in the study. Their capsule shells were produced from porcine (0.03%), bovine (61.5%), vegetable (33.5%), plant origin (0.3%), fish (0.6%) and hypromellose (4.1%). The halal certification of these capsule shells have been categorized into 7 categories; A (28.1%), B (25.3%), C (2.6%), D (35.1%), E (1.0%), F (2.2%) and G (5.7%). Bovine capsule shell has the largest percentage of use in pharmaceutical products. The largest halal certification category, D, represents capsule shell which have been certified Halal by foreign certification bodies recognized by JAKIM. CONCLUSION: A minimum usage of porcine capsule shell in preparation of pharmaceutical products is a calming fact for muslim consumers. However, the bovine capsule shell need to be examine further, to ensure the bovine hide or skin used were slaughtered according to Shariah Law. The high percentages of pharmaceutical products and capsule shells with local (JAKIM) halal certification indicate a positive attitude among manufacturers and consumers on halal certification, especially JAKIM’s.